Pendampingan Pengajaran dan Pengelolaan BIPA pada Madrasah Aliyah Internasional Al Irtiqo’ Malang - M. Isnaini; Hidayah Budi Qur'ani (BALE LITERASI, 2026)
The Indonesian Language for Foreign Speakers (BIPA) program plays a significant role in promoting the internationalization of the Indonesian language. Madrasah Aliyah Internasional Al Irtiqo' Malang requires strengthened BIPA instruction and program management to support its international educational environment. This community service program aimed to improve teachers' competencies in BIPA instruction and enhance program management. The methods included needs assessment, training, mentoring, teaching practice, and program evaluation. The results showed improved teacher understanding of BIPA instructional principles, enhanced ability to develop teaching materials for foreign learners, and more systematic program administration and planning. Participants also expressed positive responses to the mentoring activities, as they helped address challenges encountered in BIPA implementation. Overall, the program contributed to improving the quality of BIPA instruction and management and can serve as a reference for similar educational institutions.